2020
DOI: 10.3390/antiox9100906
|View full text |Cite
|
Sign up to set email alerts
|

Positive Association of Ascorbate and Inverse Association of Urate with Cognitive Function in People with Parkinson’s Disease

Abstract: Oxidative stress is thought to contribute to the aetiology of neurological disorders such as Parkinson’s disease. Ascorbate (vitamin C) is a potent antioxidant and is associated with neurological and cognitive function. In this study we assessed the ascorbate status of a cohort of people with Parkinson’s disease (n = 215), aged 50–90 years, compared with a cohort of age matched healthy controls (n = 48). The study sample’s cognitive status ranged from normal to mild cognitive impairment and dementia. There was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 57 publications
1
2
0
Order By: Relevance
“…A negative correlation between VC intake and PD progression, and a positive association with cognitive function in PD patients, have both been reported in the literature. , Most authors have suggested that the antioxidant function of VC is at the basis of these correlations. , Here, we present evidence that another pathway may be involved: the ubiquitination of GLT-1, which can be reduced by VC. Ubiquitination involves the addition of ubiquitin polypeptides to amino acids, mainly to lysines, in proteins through isopeptide bonds, which are then catalyzed by three enzymes, E1, E2, and E3.…”
Section: Results and Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…A negative correlation between VC intake and PD progression, and a positive association with cognitive function in PD patients, have both been reported in the literature. , Most authors have suggested that the antioxidant function of VC is at the basis of these correlations. , Here, we present evidence that another pathway may be involved: the ubiquitination of GLT-1, which can be reduced by VC. Ubiquitination involves the addition of ubiquitin polypeptides to amino acids, mainly to lysines, in proteins through isopeptide bonds, which are then catalyzed by three enzymes, E1, E2, and E3.…”
Section: Results and Discussionsupporting
confidence: 69%
“…A negative correlation between VC intake and PD progression, and a positive association with cognitive function in PD patients, have both been reported in the literature. 30,31 Most authors have suggested that the antioxidant function of VC is at the basis of these correlations. 32,33 Here, we present evidence that another pathway may be involved: the ubiquitination of GLT-1, which can be reduced by VC.…”
Section: T H I S C O N T E N T Imentioning
confidence: 99%
“…Ascorbate also functions in the regeneration of Vitamin E, another antioxidant, by reducing the tocopheroxyl radical [90]. A recent study demonstrated a higher proportion of hypovitaminosis C in PD patients compared to healthy controls, and that this deficiency of ascorbate was associated with worse cognitive impairment and lower MoCA scores [91]. PD patients have significantly lower serum ascorbate [92], and furthermore, reduced lymphocyte ascorbate concentration is associated with increased PD severity, as assessed by Hoehn-Yahr staging [93].…”
Section: Vitamin Cmentioning
confidence: 99%